2014
DOI: 10.1111/1759-7714.12011
|View full text |Cite
|
Sign up to set email alerts
|

Primary malignant achromic melanoma of the lung

Abstract: Currently, less than thirty cases of primary malignant melanoma of the lung have been reported in the literature. Thus, strict criteria for diagnosis have been published and include: malignant melanoma associated with bronchial epithelial changes; a solitary lung tumor; no prior history of skin, mucous membrane, intestinal or ocular melanoma; and absence of any other detectable tumor at the time of diagnosis. In this article we present a case of melanoma of the lung without evidence of extrapulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Surgical resection combined with immunotherapy, when feasible, is the main treatment for PMML; however, the prognosis for most patients is poor. 4 Lazarou et al 13 reported a case of an 82-year-old male nonsmoker with PMML who underwent total right lung resection. Postoperative rib metastases developed, and radiotherapy was administered, but the clinical response was incomplete, and the patient died 13 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection combined with immunotherapy, when feasible, is the main treatment for PMML; however, the prognosis for most patients is poor. 4 Lazarou et al 13 reported a case of an 82-year-old male nonsmoker with PMML who underwent total right lung resection. Postoperative rib metastases developed, and radiotherapy was administered, but the clinical response was incomplete, and the patient died 13 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…During the diagnosis, attention should be paid to distinguishing PMML from some similar tumours such as squamous cell carcinoma (SCC), pulmonary metastatic melanoma (PMM), and pigmented carcinoid tumour (PCT) [15][16][17]. The imaging features of primary MM are similar to those of SCC, especially when the degree of tumour differentiation is low.…”
Section: Discussionmentioning
confidence: 99%
“…This approach would be limited in cases of achromatic melanomas so they should be excluded from the category of tumors appropriated for this strategy. A possibility for their inclusion in the one - step melanoma surgery would be the use of confocal microscopy and/or cytological analysis in combination with immunohistochemical methods [ 27 ][ 28 ].…”
Section: Discussionmentioning
confidence: 99%